2008
DOI: 10.1007/s11661-008-9688-x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Behavior of Cryomilled CP-Ti Consolidated via Quasi-Isostatic Forging

Abstract: Commercially pure (CP) Ti (Grade 2 with chemical composition 0.190 wt pct O, 0.0165 wt pct N, 0.0030 wt pct C, and 0.013 wt pct Fe) was cryomilled in liquid argon and liquid nitrogen for 8 hours. The influence of the milling environment on the chemistry, grain size, and grainboundary structure of CP-Ti was studied by means of transmission electron microscopy (TEM), X-ray diffraction (XRD), and chemical analysis. The results show that the final average grain size obtained after 8 hours of cryomilling was~20 nm,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 31 publications
4
23
2
Order By: Relevance
“…Powder contamination is an inherent characteristic of cryomilling, and it may arise either from the processing media or from the atmosphere. [14,16,33,41] Carbon black, used as PCA, represents the origin of increased C content, whereas the steel milling media is the source for Fe contamination. The increased amounts of N and O are attributable to atmospheric contamination during powder handling and transport prior to chemical analysis.…”
Section: A Cryomilled Powdersmentioning
confidence: 99%
See 4 more Smart Citations
“…Powder contamination is an inherent characteristic of cryomilling, and it may arise either from the processing media or from the atmosphere. [14,16,33,41] Carbon black, used as PCA, represents the origin of increased C content, whereas the steel milling media is the source for Fe contamination. The increased amounts of N and O are attributable to atmospheric contamination during powder handling and transport prior to chemical analysis.…”
Section: A Cryomilled Powdersmentioning
confidence: 99%
“…The microstructure and mechanical behavior of cryomilled CP-Ti was studied previously by Ertorer et al [13,14] In these studies, balanced combinations of strength and ductility were reported. Also in these studies, quasi-isostatic (QI) forging was used as a consolidation and secondary deformation method.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations